International Monetary Fund Annual Report 2001 : Making the Global Economy Work for All. (Annual Report of the Executive Board; Annual Report of the Executive Board, 2001)
This 2001 Annual Report reviews economic developments in the world during FY2000. Output growth in emerging Asia picked up in 2000 as this region continued its recovery from the 1997-98 crisis. The pace of economic expansion, however, slowed from mid-2000, largely as a result of the U.S. slowdown, higher oil prices, a decline in regional equity markets, and, in some countries, concerns about delays of corporate and financial restructuring and a decline in electronics exports. The financial year 2001 saw the IMF actively engaged in the process of reform.